3D MXene-holey graphene hydrogel for supercapacitor with superior energy storage. (March 2022) - Zhu, Zhenxiang; Wang, Zhenxing; Ba, Zhaohu; Li, Xiuting; Dong, Jie; Fang, Yuting; Zhang, Qinghua; Zhao, Xin
Highlights: MXene-holey graphene hydrogel was prepared by in-situ hydrothermal reaction. The holey graphene can prevent the stacking of MXene sheets. MX-HGH delivers a specific capacity of 415 F g −1 and 597 F cm −3 . The assembled device shows a specific energy of 15.4 Wh kg −1 at 22.2 Wh L −1 . Abstract: MXene, a new two-dimensional material, has attracted much attention in the field of energy storage. Assembling it into a three-dimensional structure is an effective way to solve the self-stacking problem. However, the assembly of MXene into a three-dimensional structure inevitably reduces the density of the electrode, resulting in a low volumetric capacitance. Here, three-dimensional MXene-holey reduced graphene oxide hydrogel with hierarchical porous structure was obtained by low-temperature hydrothermal treatment, which was used as superior performance binder-free supercapacitor electrode. In the MXene-holey reduced graphene oxide hydrogel electrode, holey reduced graphene oxide can accelerate ion transport, shorten ion and electron transport pathways, and improve the gravimetric capacitance as well as the volumetric capacitance of the electrode. When MX-HGH is applied to the electrode of supercapacitor, it can release gravimetric capacitance up to 415 F g −1 and volumetric capacitance of 597 F cm −3 . This work demonstrates a practical method to construct three-dimensional MXene structures with high gravimetric capacitance and relatively high volumetric capacitance, opening up a fresh idea for the application of MXene three-dimensional structures in supercapacitors.